IMPLEMENTASI MEDIA ANIMAKER UNTUK MENINGKATKAN PENGUASAAN PECAHAN SENILAI DAN KETERLIBATAN BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA KELAS IV SD NEGERI 35 MATOBE - Rika Irawati; Syafri Ahmad; Salmaini Salmaini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This classroom action research aimed to improve students’ mastery of equivalent fractions and their learning engagement through the implementation of Animaker as a digital animation-based learning media. The study was conducted in two cycles involving 24 fourth-grade students at SD Negeri 35 Matobe. Data were collected through learning outcome tests, observation sheets, and documentation. The results showed a significant improvement in students’ understanding of equivalent fractions, supported by clear visualizations of fraction comparison, fraction transformation, and part-whole relationships provided through Animaker animations. Students became more active in discussions, asked more questions, and showed higher enthusiasm during the learning process. The average score increased from the initial low category to a higher mastery level, accompanied by an increase in classical completeness reaching the expected criteria. The animated media also enhanced classroom interaction, making abstract mathematical concepts more concrete and accessible for students. Overall, the implementation of Animaker proved effective in strengthening conceptual understanding and boosting students’ learning engagement in mathematics. This research contributes to the development of innovative media utilization in elementary mathematics learning and provides practical implications for teachers in designing more interactive, visual, and meaningful learning experiences.